Research on The Front Line Staff Recruitment Problem of HDL Catering Enterprises - Shao, Ying (International Journal of Global Economics and Management, 2024)
With the rapid development of China's catering industry, HDL catering enterprises as the leading brand in the industry, its frontline staff recruitment problems become particularly prominent. Under the background of the continuous expansion of the industry scale and the continuous improvement of the chain rate, the demand for professional talents of HDL catering enterprises is growing, especially the demand for store manager talents who are experienced and can quickly adapt to the business operation mode. However, the high turnover rate and employee turnover rate of the catering industry, coupled with the lack of competitiveness of compensation and benefits compared with other industries, as well as the repetitive and hard work of the work content, make it difficult for employees to achieve sustainable growth and career development in the work, thus aggravating the problem of talent shortage. Through literature review and current situation, this paper analyzes the problems existing in the process of recruitment of front line employees in HDL catering enterprises, and further analyzes the influence of internal management, market environment factors of employees on the recruitment effect. In order to improve the efficiency and quality of recruitment, this study puts forward strategies to optimize the recruitment process, expand diversified recruitment channels, innovate selection methods and improve the professional quality of recruitment teams.